Evaluation of Neutralizing Efficacy of Acorus calamus and Withania somnifera Root Extracts Against Bangarus caeruleus Venom: Plant Neutralizing Efficacy for Snake Venom - Meenatchisundaram, Subramani; P, Sindhu; Thangapandian, Veerapandian (Biological Sciences - PJSIR, 2011)
Acorus calamus and Withania somnifera root extracts when tested against Bangarus caeruleus venom, both the plant extracts neutralized various pharmacological activities induced by B. caeruleus venom. About 0.12 mg of A. calamus and 0.15 mg of W. somnifera root extracts completely neutralized the lethal activity of 2LD50 of B. caeruleus venom. Various pharmacological activities like haemorrhagic, coagulance, edematic, fibrionlytic and phospholipase activities were effectively neutralized by both the extracts.